SIX SIGMA DALAM PENGENDALIAN KUALITAS PRODUK KERIPIK PISANG DI PASURUAN - Muti, Asri Amalia; Ahmad, Nofan Hadi; Sari, Tri Novita (JURNAL ILMIAH TEKNOLOGI INDSUTRI (SAINTI), 2023)
Small companies that do not pay attention to product quality will experience marketing problems such as decreased product sales. Therefore, quality control is required for each product. Banana chips, for example, are considered very difficult to manufacture and often experience product defects. The cause of product failure is a weakness of a business today. The cause of this failure is unknown until now. Banana stick production based on data from August to September 2020 shows the number of defective products is approximately 28,875 kg of the total production, which is 323 kg. Therefore this research is intended to determine the factors that affect production defects in banana sticks. While the benefit of this research is to be able to control the factors that affect defects in banana sticks and can later increase profits and work productivity. The Six Sigma method is one of the tools commonly used in product quality control, where the concept of this method is to set quality standards of up to 3.4 rejects per million possibilities. Based on the results of banana chip defect data, it was found that the type of defect was sluggish with a percentage of 61% and the type of defect was burnt with a percentage of 39%. Factors that affect the two defects include human factors, materials, machines. The suggestion from this research is that of the three most influencing factors are humans, materials and machines. Companies need to plan improvements in stages so that in the future these products can achieve lean production.